Increased production of chitinase by a Paenibacillus illinoisensis isolated from Brazilian coastal soil when immobilized in alginate beads - da Silva, Francenya Kelley Lopes; de Sa Alexandre, Artur Ribeiro; Casas, Ariadine Amorim; Ribeiro, Maycon Carvalho; de Souza, Keili Maria Cardoso; Soares, Enio Saraiva; Dos Santos Junior, Samuel Rodrigues; Vieira, Jose Daniel Gonçalves; Amaral, Andre Correa (Folia microbiologica, 2022)
The accumulation of chitin waste from the seafood industry is a serious environmental problem. However, this residue can be degraded by chitinases and its subproducts, such as chitosan, economically exploited. In this study, a chitinase producer bacteria, identified as Paenibacillus illinoisensis, was isolated from the Brazilian coastal city of Terra de Areia - Rio Grande Do Sul (RS) and was immobilized within alginate beads to evaluate its chitinase production. The alginate beads containing cells presented an average size of 4 mm, 99% of immobilization efficiency and increased the enzymatic activity in 40.71% compared to the free cells. The biomass during enzymatic production increased 62.01% and the total cells leaked from the alginate beads corresponded to 6.46% after 96 h. Immobilized cells were reused in a sequential batch system and remained stable for production for up to four 96-h cycles, decreasing only 21.04% of the initial activity at the end of the fourth cycle. Therefore, the methodology used for cell immobilization resulted in adequate beads to maintain cell viability during the enzymatic production, increasing enzymatic activity, showing low cell leakage from the support and appropriate recyclable capacity.
Keywords: Brazílie; Cellular immobilization; Chitin; algináty; Soil; Alginate; půda; Ionotropic Gelation; Alginates; Chitinases; Chitinase; chitinasy; kyseliny hexuronové; Hexuronic Acids; Biopolymers; Brazil